2021
DOI: 10.1063/5.0030090
|View full text |Cite
|
Sign up to set email alerts
|

Raman spectroscopic studies of ortho-xylene under laser driven shock and static compression

Abstract: Ortho-xylene (o-xylene), a derivative of benzene and an important aromatic compound is applied as an anti-knocking agent in automobiles and jet engines. Knocking being a dynamical phenomenon that occurs at very high temperatures and high pressures, here we have reported the pump–probe technique based time-resolved Raman spectroscopy studies under laser-driven shock compression (high temperature and high pressure) along with the numerical simulation to understand the molecular level response of o-xylene under s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…These temperature values are estimated from the simulation. Theiry et al [11] and Rao et al [15] have also reported similar temperature effects on the benzene sample and found the phase transitions occurred in benzene at higher pressure in case of shock experiments compared with static compression due to higher shock temperature. In the inset of Figure 4, we have also included the effect of the reflected shock pressure on the Raman modes (denoted by *), which were observed during the time-resolved measurements discussed in the previous section.…”
Section: Raman Studies With Varying Strength Of Shock Compressionmentioning
confidence: 71%
See 1 more Smart Citation
“…These temperature values are estimated from the simulation. Theiry et al [11] and Rao et al [15] have also reported similar temperature effects on the benzene sample and found the phase transitions occurred in benzene at higher pressure in case of shock experiments compared with static compression due to higher shock temperature. In the inset of Figure 4, we have also included the effect of the reflected shock pressure on the Raman modes (denoted by *), which were observed during the time-resolved measurements discussed in the previous section.…”
Section: Raman Studies With Varying Strength Of Shock Compressionmentioning
confidence: 71%
“…Schmidt et al [14] have experimented on benzene using gas gun/powder gun and reported two phase transitions at 1.2 and 4 GPa. Recently, Rao et al [15] have performed static and dynamic compression experiments on benzene up to 14.3 GPa and reported two phase transitions at 0.3 and 2.3 GPa, respectively. Benzene has been explored very extensively; however, other compounds of BTEX have not been explored thoroughly.…”
Section: Introductionmentioning
confidence: 99%